Accelerated atherosclerosis in anti-neutrophil cytoplasmic antibody-associated vasculitis: case report - Uribe Ruíz, Natalia Andrea (2024)
Accelerated atherosclerosis has become a complication of multiple autoimmune diseases, among which Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis stands out. The case of a patient with hypertension, diabetes, and chronic kidney disease of unknown etiology is described, who presented two acute coronary syndromes with a difference of only six months, with rapid progression of coronary involvement, in search of the etiology with an increase in inflammatory response markers, tomography with usual interstitial pneumonia and positive antibodies directed against myeloperoxidase (anti-MPO) that led to the diagnosis of microscopic polyangiitis (PAM). The situation in which a timely diagnostic suspicion is crucial since early treatment has a notable impact on the course and prognosis of the disease.